Pendekatan Praksis-Teologis dalam Fondasi Pendidikan Kristiani - Justice Zeni Zari Panggabean (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2018)
This article has some purposes; they are: first, a description of the about theoretical study of a theological practice approach; secondly, explained an implication theological practice approach to the Christian religion education foundation; and thirdly, described a religion studies foundation of Christians in theological practice approach. The method used in this article is an analysis-descriptive of literature available related to the problem that discussed. This research concluded that a practical approach theological in education foundation the Christian religion came into existence from the application of the truth in the life of that can be used with confidence as cornerstones biblical, and search for clues definitive from general principles offered by theology.AbstrakTulisan ini memiliki beberapa tujuan, yaitu: pertama, mendeskripsikan kajian teoretis pendekatan praksis teologis; kedua, menjelaskan implikasi praksis-teologis fondasi pendidikan Agama Kristen. Metode yang digunakan adalah analisis deskriptif terhadap kajian pustaka yang berkaitan dengan tema fondasi Pendidikan Agama Kristen. Penelitian ini memiliki kesimpulan bahwa pendekatan praktis teologis dalam fondasi pendidikan agama Kristen terwujud dari penerapan kebenaran ke dalam kehidupan yang bisa digunakan dengan percaya diri sebagai fondasi Alkitabiah, dan mencari petunjuk definitif dari prinsip-prinsip umum yang ditawarkan oleh teologi.